Kontribusi Work Engagement terhadap Turnover Intention pada Karyawan Perusahaan Ritel - Nadya Putri; Tuti Rahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
High turnover rates are a problem in the retail sector because they can disrupt operational stability. One factor related to turnover is turnover intention, which is influenced by various psychological aspects, including work engagement. This study aims to determine the contribution of work engagement to turnover intention among employees of a retail company in Bukittinggi. This study aims to determine the contribution of work engagement to turnover intention among retail employees. This study uses an explanatory method with a quantitative approach. The study population consisted of 82 employees who became the sample of this study. Data collection was carried out using psychological scales, namely the Utrecht Work Engagement Scale (UWES-9) and the Turnover Intention Scale (MTIS-6). Data analysis was carried out through simple linear regression analysis with the help of JASP version 0.95.4. The results illustrate that work engagement has a significant contribution to turnover intention with significance (p < 0.001). The contribution obtained is positive, indicating that the higher the work engagement, the lower the turnover intention. This finding implies that work engagement does not always reduce turnover intention, but is influenced by working conditions and the organizational context.